KAJIAN ETNOMATEMATIKA ALAT MUSIK SENGGAYONG DI DESA PANGKALAN BUTON KECAMATAN SUKADANA KABUPATEN KAYONG UTARA - Kharina Shima A. Simanjuntak; Zubaidah R; Silvia Sayu (UNIVERSITAS TANJUNGPURA, 2022)
This study aims to reveal ethnomathematical activities and mathematical concepts on senggayong musical instruments in Pangkalan Buton Village, Sukadana District, North Kayong Regency. The method used is descriptive method. While the form of research is a form of qualitative research. The subjects in this study are people who are considered to be able to assist in providing information and data about senggayong musical instruments, namely the makers, players, and conservationists of senggayong musical instruments. Data collection techniques using observation, interviews, and documentation. Data analysis techniques based on Miles & Huberman, namely data reduction, data presentation, as well as drawing conclusions and verification. The results of data analysis show that there are ethnomathematical activities and mathematical concepts on senggayong musical instruments, namely counting activities that occur when counting the bamboo to be used, activities of measuring each piece of bamboo used, designing activities of making senggayong musical instruments, activities of determining a meaningful location in taking Bamboo that is suitable for making senggayong musical instruments is bamboo that is exposed to sunlight, the activity of playing a senggayong musical instrument and the activity of explaining the process in making and playing the instrument. Then the mathematical concepts that were found based on the shape and beat of the senggayong musical instrument, namely in the form of a geometric shape of a tube shape and its beat, the concepts of arithmetic sequences and geometric sequences were obtained.